Does feedback on personal investment success help? - Steffen Meyer; Linda Urban; Sophie Ahlswede (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
In a field study with more than 1.500 customers of an online-broker we test what happens when investors receive repeated feedback on their investment success in a monthly securities account report. The reports show investors' last year's returns, costs, their current level of risk and their portfolio diversification. We find that receiving a report results in investors trading less, diversifying more and having higher risk-adjusted returns. Results are robust to controlling for potential play money accounts and changes in report designs. We also find that investors who are less likely to subscribe equally benefit from the report.
Keywords: D14; G11; G28; 330; household finance; field study; individual investors; reporting; investment mistakes; regulation